Social Acceleration: A Challenge for Companies? Insights for Business Ethics from Resonance Theory - Bettina Hollstein; Hartmut Rosa (Journal of Business Ethics, 2023)
In modern capitalist societies, companies are exposed to enormous pressure to accelerate. However, it has increasingly become apparent that the social and economic acceleration which is the result of systemic imperatives tends to produce conflict both on the micro-level of personal temporal patterns and rhythms and on the macro-ecological level, where it tends to undermine the proper times for natural regeneration and reproduction. Corporations are increasingly called upon as corporate citizens to fulfil their responsibilities to stakeholders such as employees or ecosystems. Business ethics approaches therefore seek to develop strategies for fulfilling this responsibility in view of these conflicts created by social acceleration. In this contribution, we first present a diagnosis of acceleration imperatives for companies based on a sociological analysis of social acceleration. Then we examine the normative aspects of conflicts created by acceleration for employees and the ecosphere using the sociological conception of resonance. We attempt to articulate conceptually the normative requirements for a business ethics which are capable of dealing with the problems of social acceleration in corporations with a particular focus on a resonant stakeholder approach.
Keywords: 300; Social acceleration; Resonance; Stakeholder ethics; Stress; Sustainability